PATU9 Seasonal variation in multiple sclerosis relapse. Issue 11 (22nd October 2010) - Baker, K; Pickersgill, T; Robertson, N; Cossburn, M; Ben-Shlomo, Y; Tilling, K; Hirst, C; Ingram, G
Abstract : The aetiology of events initiating relapse in MS is unclear but it has been postulated that environmental factors linked to climatic change may act as triggers. We analyse month of relapse from data collected prospectively from a large population-based cohort of patients over a 5-year-period (2005–9) and examine associations with climatic variables. A total of 1473 relapses from 617 patients were modelled using Poisson regression. In order to minimise recall bias subgroup analyses were also performed on relapses from patients attending a self-referral relapse clinic (n=722), and surveyed by validated questionnaire (n=221). Compared to April (baseline) a trough in relapses was observed in September (relapse ratio 0.76, 95% CI 0.58 to 0.99, p=0.04) and January (relapse ratio 0.75, 95% CI 0.56 to 0.98, p=0.03). In addition there was a nonsignificant peak in relapses in June (relapse ratio 1.23, 95% CI 0.98 to 1.56, p=0.08). The pattern of relapses could be modelled by a sinusoidal curve p=0.0003. Furthermore the number of monthly sunshine hours predicted relapse frequency (relapse ratio 1.06, 95% CI 1.00 to 1.12, p=0.04 per standard deviation unit). The summer relapse frequency peak was replicated in clinic subgroup data but not in the questionnaire subgroup. This is the largest seasonal analysis of relapses and supports findings from prior small European studies of summer peaks and autumnal troughs. The causes for this seasonal variation remain unclear though sun exposure may be relevant.